The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1111/bcp.13646
|View full text |Cite
|
Sign up to set email alerts
|

Interaction betweenABCG2 421C>Apolymorphism and valproate in their effects on steady‐state disposition of lamotrigine in adults with epilepsy

Abstract: This study is first to indicate a potentially relevant interaction between ABCG2 421C>A polymorphism and valproate in their effects on lamotrigine disposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“…These studies have combined several simplistic situations including polymorphisms or polymorphisms plus VPA, which may not have been sufficient to distinguish and weigh multiple factors in practical use. In our final model, ABCG2 421C > A had no effect on LTG concentrations, similarly to the results of the Domjanovic et al study (Domjanovic et al, 2018), whereas ABCG2 34G > A was found to be a significant covariate.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…These studies have combined several simplistic situations including polymorphisms or polymorphisms plus VPA, which may not have been sufficient to distinguish and weigh multiple factors in practical use. In our final model, ABCG2 421C > A had no effect on LTG concentrations, similarly to the results of the Domjanovic et al study (Domjanovic et al, 2018), whereas ABCG2 34G > A was found to be a significant covariate.…”
Section: Discussionsupporting
confidence: 87%
“…However, the current opinion on whether ABCG2 421C > A is a predictor of LTG concentration remains controversial. Zhou et al (2015) and Shen et al (2016) have observed similar associations between ABCG2 -421AA and higher dose-normalized LTG concentrations in patients by using multiple linear regression models; in contrast, Domjanovic et al (2018) have demonstrated that the ABCG2 421A allele has no effect on LTG concentrations, but the variant allele effect would increase with incremental VPA troughs. These studies have combined several simplistic situations including polymorphisms or polymorphisms plus VPA, which may not have been sufficient to distinguish and weigh multiple factors in practical use.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Finally, the variables used in our model, though readily available, are all non-genetic factors. The effects of genetic polymorphisms on LTG pharmacokinetics have been widely explored in previous studies, but have yielded some conflicting findings 48,49 . Thus, more variables (e.g., genetic factors) needed to be included in the model.…”
Section: Discussionmentioning
confidence: 99%